Towards optimising children's capability and tackling relative child poverty in high-income countries: the cases of Japan, Sweden and the UK since 2000 - Hajime Takeuchi; Sung-Hee Lee; Anneli Ivarsson (Taylor & Francis Group, 2022)
Background We question why child poverty still prevails even in high-income countries, such as Japan, Sweden and the United Kingdom. We address the intersection between social relations and individual experiences that should be considered when optimising children's capability. Objectives The study is therefore aimed at exploring compensatory societal actions taken to optimise children's capability among these affluent countries. In order to do so, we operationalised children's capability by including key societal domains along with statistical indicators and variables from relevant sources. Methods A secondary quantitative method was adopted by drawing upon data sources from 2000 up to almost 2020 from the Organisation for Economic Co-operation and Development, the World Bank and the United Nations Children's Fund, with these being complemented by governmental data. Given a lack of currently available and comparable data for those three countries, four key societal domains were explored in an absolute descriptive analysis. Results It is obvious that child poverty prevailed over the focal 20 years in these three high-income countries. Also, the exploratory data analysis revealed a lack of sufficient supporting social services in each societal domain. This demonstrates that optimising children's capability should not just be about subsidising economic resources, but also supporting all initiatives aimed at addressing the lack of interactions between each domain of children's capability. Conclusions The study shows how essential it is to consider societal compensatory measures along with supporting the financial circumstances. We therefore argue that optimising children's capability should not only be about subsidising economic resources, but also ensuring adequate social resources and relations.